Studi Kepatuhan Penggunaan Obat Antihiperglikemik Oral pada Pasien Diabetes Melitus Tipe 2 di Puskesmas Cikutra Lama 1 Bandung - Diva Rachmadita Kusumawardani; Fetri Lestari; Umi Yuniarni (UNISBA Press, 2022)
Abstract. Diabetes mellitus is a lifelong metabolic illness that can occur in all levels of society, and causes the rising of glucose levels in the bloodstream. Normalizing the glucose levels can be done either by therapy of changing the lifestyle or ingesting oral antihyperglycemic medicine. The patient using oral antihyperglycemic medicine has to take the medicine regularly and cannot miss any of it, thus the adherence of the patient is important. This study was done to depict adherence and reasons of disobedience on ingesting oral hyperglycemic medicine of Type 2 Diabetes Mellitus patients in Puskesmas Cikutra Lama Bandung using MMAS-8 type questionnaire on 25 adults as subjects with criteria such as man or woman, in the range of 18-65 year old, and is treated with oral antihyperglycemic on January 2021-May 2022. This study was carry out on May 2022 with interview method. MMAS-8 is used because of its objectiveness and can be used to both identify and measure how the patients adhere to ingesting oral hyperglycemic medicine. From 25 subjects, 36% has